Efficient Synthesis of (Z)-4-((Substituted phenylamino)methylidene)isoquinoline-1,3(2H,4H)-diones Using the Eschenmoser Coupling Reaction - Marek, Lukáš; Váňa, Jiří; Svoboda, Jan; Svobodová, Markéta; Hanusek, Jiří (Synthesis, 2023)
A novel synthetic strategy involving the Eschenmoser coupling reaction of 4-bromoisoquinoline-1,3(2H,4H)-diones with substituted thioformanilides, thioacetanilides, and thiobenzanilides gave 18 (Z)-4-((substituted phenylamino)methylidene)isoquinoline-1,3(2H,4H)-diones. The reaction occurs under mild conditions (DMF or MeCN, 25–60 °C) without any base or thiophile and in good yields (43–95%). Furthermore, for the synthesis of starting thioformanilides carrying basic substituents, a new thioacylation protocol was developed that involves a thioacylating agent formed from carbon disulfide and lithium triethylborohydride.
Keywords: Eschenmoser coupling reaction; 4-bromoisoquinoline-1,3(2H,4H)-diones; thioamides; thioacylation; bromination